It's a Man's World (Wide Web) A Critical Analysis of Online Misogyny and Hate Speech - Spallaccia, Beatrice (Alphabet, 2020)
"Abusive posts on social media target women engaged in online conversation with words and images that affirm patriarchal ideologies and fixed gender identities, to maintain cyberspace as a man's world. This book investigates online misogyny as a pervasive yet little-researched form of hate speech. By focusing on six cases of cyber harassment directed at women in Australia, Italy, and the United States, this qualitative analysis reveals specific discursive strategies along with patterns of escalation and mobbing that often intertwine gender-based harassment with racism, homotransphobia, xenophobia, and ageism. The author provides a taxonomy of negative impacts on targets that integrates findings across cases and indicates pathways from hate speech to harms. The study suggests an urgent need for effective measures against the threat posed by misogynistic hate speech to individuals and to an open, respectful forum for online communication. Beatrice Spallaccia is Research Fellow and Adjunct Professor at the University of Bologna (Department of Interpreting and Translation, Forlì Campus). In 2017 she completed an International PhD (University of Bologna - Monash University) with a thesis on online misogyny. Her academic research focuses on gendered hate speech, anti-gender discourses in Europe, and the translation of LGBTQ-themed literature for young readers."